Comparison of physiological and psychological well-being in physical active and sedentary women in Iran. - Parichehr, Hanachi; Parvaneh, Nazar Ali; Rezayi, Najmeh; Abd Latiff, Latiffah (Canadian Center of Science and Education, 2010)

(untitled)
Researcher has shown that habitual physical activity enhances both physiological and psychological health. The objective of the paper was to comparison of Physiological and psychological well-being in physical active and sedentary women in Iran. Data of 2500 subjects (aged 15-55 years) from a five-state cross sectional study was used in this analysis. Psychological and Physiological well being was assessed using 28-item General Health Questioner (GHQ). It was found that 62.4% single and 69.8% married had good psychological well being. More single (13.5%) than married (5.9%) showed poor psychological well being. There was significant difference between psychological well being and marital status (p<0.05). The results shows that about 61.4% of not working and 63.6% of working respondents with good psychological well being while 16.2% of not working and 10.6% of working respondents had poor psychological well being. There was significant difference between psychological, well being and working status (p<0.05). There was not significant difference between psychological well being and education of the respondents. More active women respondents (68.2%) were found to have good psychological well being compared to 56.1% of the respondents who did not. There was a significant difference between psychological well being, age and physical activity of respondents (p<0.05). The results indicated association between physiological and psychological well-being, as measured using a variety of psychological inventions and regular physical exercise.